Note on the Fascinating Fermat Numbers - Mulatu, Lemma,; Mengistie, Noel; Mulatu, Samera (IJRDO -JOURNAL OF MATHEMATICS, 2018)
A Fermat number is an integer of the form      n ≥ 0The Fermat numbers are named after the French mathematician Pierre de Fermat (1601 – 1665) who first studied numbers  of such form.In this paper we investigated some  interesting properties of the Fermat numbers.The first five Fermat numbers are 1,5,17,257 and 65537.The Main ResultsThe following two theorems deal with the recursive properties of the Fermat Numbers.